Alumina foam ceramic and method for producing the same
Patent Information
- Application Number
- CN202610981567.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-02
- Publication Date
- 2026-10-16
AI Technical Summary
[0006]本发明针对现有有机泡沫浸渍法制备氧化铝泡沫陶瓷存在的孔结构可控性差、固有结构缺陷补强机制缺失两大核心技术瓶颈,旨在提供一种孔结构可控、性能稳定的氧化铝泡沫陶瓷及其制备方法,通过模板复合预处理、梯度固含量多次挂浆、真空辅助浸渍、离心甩浆以及梯度分段干燥与烧结的协同作用,实现制品孔隙率与力学强度的协同可控
一、精准调控三维孔结构,有效改善批次一致性。通过聚氨酯模板深度除隔膜与亲水性复合预处理,彻底消除内部残留网状隔膜并显著改善与氧化铝极性浆料的润湿性能;同时采用差异化浸渍-离心甩浆精准控量工艺替代传统粗放的辊压/手动排浆方式,实现浆料附着量的定量调控,从根源解决了挂浆不均、漏涂、局部堵孔等缺陷,制备的坯体孔筋饱满均匀,有效提高产品批次稳定性与一致性。
Smart Images

Figure CN122916624A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of porous ceramic material preparation, specifically to an alumina foam ceramic and its preparation method. Background Technology
[0002] Alumina foam ceramics, as a typical porous oxide ceramic, have become a key material in high-temperature filtration, catalyst carriers, molten metal purification, and industrial thermal insulation due to their inherent advantages such as high temperature resistance, corrosion resistance, low thermal conductivity, and three-dimensional interconnected network structure. The organic foam impregnation method has become the mainstream process for the industrial production of alumina foam ceramics because of its simplicity, low equipment investment, and ease of large-scale production.
[0003] However, the existing organic foam impregnation method for preparing alumina foam ceramics still faces two major technological bottlenecks: Firstly, the controllability of the pore structure is poor. Traditional processes generally employ a crude slurry application method, combining atmospheric pressure impregnation with roller pressing / manual slurry discharge, which makes it difficult to precisely control the amount of slurry adhered. Insufficient slurry application can lead to thinner pores, poor continuity of the three-dimensional skeleton, and difficulty in meeting mechanical performance standards. Excessive slurry application results in excessive slurry accumulation, which can easily cause local pore blockage and a significant decrease in the porosity of the finished product. At the same time, most polyurethane templates are treated with low-concentration room-temperature alkaline solutions, leaving residual internal mesh diaphragms and strong surface hydrophobicity, resulting in poor interface compatibility with alumina slurry and further exacerbating the problems of uneven slurry application and uncontrolled pore structure.
[0004] Secondly, there is a lack of inherent structural defect reinforcement mechanisms. The organic template impregnation method itself has inherent structural characteristics; after removing the polyurethane skeleton, hollow pores naturally form. At the same time, during the low-temperature adhesive removal process, the organic components decompose and generate gas, which easily forms secondary defects such as pores and microcracks on the surface and inside of the pores. Traditional processes generally adopt a single molding mode of "one-time slurry application and one-step high-temperature sintering," without establishing a gradient reinforcement and repair mechanism for the above-mentioned defects. Ultimately, this results in the product being unable to achieve a synergistic improvement in mechanical properties while maintaining high porosity, making it difficult to meet the long-term stable service requirements of high-end industrial scenarios.
[0005] Therefore, developing a method for preparing alumina foam ceramics that can precisely control the pore structure, effectively repair inherent process defects, and simultaneously achieve both high porosity and high strength has become a pressing technical problem to be solved in this field. Summary of the Invention
[0006] This invention addresses two core technical bottlenecks in the preparation of alumina foam ceramics using existing organic foam impregnation methods: poor controllability of pore structure and lack of reinforcement mechanisms for inherent structural defects. It aims to provide an alumina foam ceramic with controllable pore structure and stable performance, along with its preparation method. Through the synergistic effects of template composite pretreatment, multiple slurry application with gradient solid content, vacuum-assisted impregnation, centrifugal slurry removal, and gradient segmented drying and sintering, the porosity and mechanical strength of the product are synergistically controllable.
[0007] The technical method of the present invention is as follows: A method for preparing alumina foam ceramic includes the following steps: S1. Polyurethane foam composite pretreatment: Take polyurethane foam and perform deep membrane removal treatment and hydrophilic modification treatment in sequence to obtain modified template. S2. Gradient solid content slurry preparation: According to the requirements of the slurry coating process, deionized water is used as solvent, alumina powder and sintering aid are used as main raw materials, and dispersants and binders are added to prepare alumina slurries with different solid contents, including a primary slurry with a high solid content and at least one subsequent slurry with a low solid content. S3. Primary slurry application, drying and pretreatment of the green body: The modified template is subjected to atmospheric pressure impregnation, centrifugal slurry application, and gradient segmented drying using the primary slurry with high solid content; the dried green body is then subjected to either non-sintering, low-temperature sintering, or first high-temperature sintering treatment. S4. Subsequent slurry coating, drying, and sintering: Based on the preset target porosity and mechanical property requirements, the pretreated green body undergoes at least one subsequent slurry coating process, and the following steps are performed according to the pretreated state of the green body: S4.1 For the pre-treated green body selected in step S3, use a subsequent slurry with a low solid content to sequentially perform atmospheric pressure impregnation, centrifugal slurry application, and gradient staged drying before the first high-temperature sintering; or S4.2. For the green body pretreated by low-temperature sintering or first high-temperature sintering in step S3, use a subsequent slurry with a lower solid content for vacuum impregnation, centrifugal slurry application, and gradient segmented drying, followed by second high-temperature sintering; or S4.3 After completing step S4.1 or step S4.2, if the preset target porosity and mechanical properties are not achieved after one subsequent slurry application and corresponding sintering, step S4.2 is repeated with a slurry having a further reduced solid content to perform the next subsequent slurry application and second high-temperature sintering until the preset performance requirements are met, and the finished alumina foam ceramic product is obtained. Wherein, the first high-temperature sintering includes a low-temperature polyurethane template removal stage and a first high-temperature sintering densification stage, and the second high-temperature sintering only includes a second high-temperature sintering densification stage. Within the temperature range of 20–650℃, the heating rate of the second high-temperature sintering is higher than that of the first high-temperature sintering.
[0008] Optionally, in step S1, the deep membrane removal process includes: treating the polyurethane foam with an alkaline solution in a water bath; wherein the alkaline solution is a sodium hydroxide solution with a concentration of 8–12 mol / L, the water bath temperature is 80–90°C, and the water bath heating time is 5–7 hours. The hydrophilic modification process includes: immersing the polyurethane foam after deep membrane removal treatment in a polymer solution at room temperature; wherein the immersion time at room temperature is 10-14 hours, and the polymer solution includes one or more of polyvinyl alcohol aqueous solution, polyvinylpyrrolidone aqueous solution, and hydroxyethyl cellulose.
[0009] Optionally, the sintering aid is silicon dioxide; the binder is alkaline silica sol; and the dispersant is ammonium polyacrylate.
[0010] Optionally, when the slurry is applied twice, the alumina slurry with different solid contents includes: a primary slurry with a solid content of 60wt% to 70wt%, and a secondary slurry with a solid content of 45wt% to 55wt%; when the slurry is applied three times, the alumina slurry with different solid contents includes: a primary slurry with a solid content of 60wt% to 70wt%, a secondary slurry with a solid content of 45wt% to 55wt%, and a tertiary slurry with a solid content of 40wt% to 50wt%.
[0011] Optionally, when the solid content of the slurry is 60wt%–70wt%, the mass ratio of alumina to silica as a sintering aid is 7–9:1–3. Based on the total mass of alumina and silica powder, 3wt%–3.5wt% of alkaline silica sol is added as a binder, and 2wt%–4wt% of ammonium polyacrylate is added as a dispersant. When the solid content of the slurry is 45wt%–55wt%, the mass ratio of alumina to silica as a sintering aid is 7–9:1–3. Based on the total mass of alumina and silica powder, 3wt%–3.5wt% of alkaline silica sol is added as a binder, and 2wt%–4wt% of ammonium polyacrylate is added as a dispersant. Based on the total mass of silica powder, 2wt% to 3wt% of alkaline silica sol is added as a binder, and 1wt% to 3wt% of ammonium polyacrylate is added as a dispersant; when the solid content of the slurry is 40wt% to 50wt%, the mass ratio of alumina to silica as a sintering aid is 7 to 9: 1 to 3, and based on the total mass of alumina and silica powder, 2wt% to 3wt% of alkaline silica sol is added as a binder, and 1wt% to 3wt% of ammonium polyacrylate is added as a dispersant.
[0012] Optionally, the preparation of the alumina slurry includes: mixing and dissolving the binder, dispersant and deionized water, adding alumina and sintering aid and mixing, and then continuously stirring at a speed of 150-200 r / min for 4-8 hours.
[0013] Optionally, the atmospheric pressure impregnation and slurry application step in step S3 specifically includes: The slurry is applied manually and / or by centrifugal coating to ensure that the slurry is evenly coated on the surface of the modified template prepared in S1. The steps of atmospheric pressure impregnation and centrifugal slurry removal in step S4 specifically include: The pre-treated green body from step S3 is completely immersed in the subsequent slurry with a low solid content. It is gently shaken and immersed for 1-3 minutes until no obvious air bubbles escape. Then, it is centrifuged at 100-150 r / min to remove the slurry. In 1 to 3 minutes, excess slurry on the surface of the billet is removed, and the subsequent slurry is evenly coated on the pores and surface of the billet. The vacuum impregnation and centrifugal slurry application steps in step S4 specifically include: The pre-treated green body, which underwent low-temperature sintering or first high-temperature sintering in step S3, is completely immersed in at least one subsequent slurry and transferred into a vacuum drying oven. The vacuum level is adjusted to 0.2–0.6 atm and maintained at that pressure for 10–20 minutes to allow the subsequent slurry to fully penetrate the green body. Subsequently, the slurry is centrifuged at 100–300 r / min for 2–4 minutes to remove excess slurry from the surface of the green body and ensure uniform slurry distribution on the surface of the pores and ribs. The vacuum environment eliminates residual air in the pores of the green body, reduces the apparent viscosity of the slurry, and achieves deep penetration and defect filling of the green body.
[0014] Optionally, the gradient segmented drying steps include: A1, room temperature pre-drying: placing the pre-dried green body in a room temperature environment with natural ventilation for 10-14 hours; A2, low temperature constant temperature drying: transferring the pre-dried green body into an oven and maintaining a constant temperature of 55-75℃ for 2-6 hours; A3, high temperature thorough drying: raising the temperature of the pre-dried green body to 110-130℃ and maintaining a constant temperature for 2-6 hours until the quality of the green body is constant.
[0015] Optionally, the low-temperature sintering step includes: heating the dried green body from 20°C to 150°C at a rate of 2-4°C / min, from 150°C to 180°C at a rate of 1-3°C / min, from 180°C to 220°C at a rate of 0.5-1.5°C / min, from 220°C to 250°C at a rate of 0.25-0.75°C / min, from 250°C to 420°C at a rate of 0.5-1.5°C / min, from 420°C to 650°C at a rate of 1-3°C / min, from 650°C to 950°C at a rate of 2-4°C / min, holding at 950°C for 1-3 hours, and cooling from 950°C to 500°C at a rate of 2-4°C / min, followed by furnace cooling.
[0016] Optionally, the first high-temperature sintering step includes: heating the dried green body from 20°C to 150°C at a rate of 2-4°C / min, from 150°C to 180°C at a rate of 1-3°C / min, from 180°C to 220°C at a rate of 0.5-1.5°C / min, from 220°C to 250°C at a rate of 0.25-0.75°C / min, from 250°C to 420°C at a rate of 0.5-1.5°C / min, from 420°C to 650°C at a rate of 1-3°C / min, from 650°C to 1300°C at a rate of 2-4°C / min, holding at 1300°C for 1-3 hours, cooling from 1300°C to 500°C at a rate of 2-4°C / min, and cooling in the furnace.
[0017] Optionally, the second high-temperature sintering step includes: heating the dried green body from 20°C to 950°C at a rate of 4-6°C / min, heating it from 950°C to 1300°C at a rate of 2-4°C / min, holding it at 1300°C for 1-3 hours, cooling it from 1300°C to 500°C at a rate of 2-4°C / min, and cooling it in the furnace.
[0018] The present invention also provides an alumina foam ceramic, which is obtained by the above-described method for preparing alumina foam ceramic.
[0019] The beneficial effects of this invention are: I. Precise control of three-dimensional pore structure effectively improves batch consistency. By using a polyurethane template for deep membrane removal and hydrophilic composite pretreatment, residual internal mesh membranes are completely eliminated, and the wetting performance with alumina polar slurry is significantly improved. At the same time, a differentiated impregnation-centrifugal slurry control process is adopted to replace the traditional rough roller pressing / manual slurry discharge method, realizing quantitative control of slurry adhesion. This fundamentally solves defects such as uneven slurry coating, missed coating, and local pore blockage. The prepared green body has full and uniform pores, effectively improving the batch stability and consistency of the product.
[0020] II. Gradient reinforcement of inherent structural defects, synergistically improving porosity and strength. A differentiated reinforcement system with multiple coatings of gradient solids content slurry was established: high solids content slurry rapidly builds a continuous three-dimensional skeleton, while medium and low solids content slurry, combined with vacuum impregnation process, fully penetrates and fills hollow pores and defects such as air bubbles and microcracks caused by glue removal; combined with gradient segmented drying and differentiated sintering regime, coating cracking and pore collapse are effectively avoided, significantly enhancing the mechanical strength of the product while maintaining high porosity. This solves the industry problem that traditional processes cannot simultaneously achieve both porosity and mechanical properties, and can stably meet the long-term service requirements of high-end industrial scenarios such as high-temperature filtration and catalyst carriers. Attached Figure Description
[0021] Figure 1 This is a flow chart of the alumina foam ceramic preparation process of the present invention; Figure 2 The following are comparison images of the polyurethane foam before and after alkaline treatment according to the present invention: (a) is the image before treatment, and (b) is the image after treatment. Figure 3 The following are comparison diagrams showing the effects of manual and centrifugal slurry application in this invention: (a) is a manual slurry application diagram, and (b) is a centrifugal slurry application diagram. Figure 4 This is a low-temperature sintering process curve diagram from an embodiment of the present invention; Figure 5 This is a graph showing the first high-temperature sintering process in an embodiment of the present invention; Figure 6 This is a graph showing the second high-temperature sintering process in an embodiment of the present invention; Figure 7 Macroscopic morphology of alumina foam ceramics prepared by different processes: (a) one high-temperature sintering; (b) one low-temperature sintering + two high-temperature sintering; (c) one no-sintering + two high-temperature sintering + three high-temperature sintering; Figure 8 Microscopic morphology of alumina foam ceramics prepared by different processes: (a) one high-temperature sintering; (b) one low-temperature sintering + two high-temperature sintering; (c) one no-sintering + two high-temperature sintering + three high-temperature sintering; Figure 9 Porosity and compressive strength of alumina foam ceramics prepared by different processes: (a) one-time high-temperature sintering; (b) one-time low-temperature sintering + two-time high-temperature sintering; (c) one-time no-sintering + two-time high-temperature sintering + three-time high-temperature sintering. Detailed Implementation
[0022] The technical solution of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0023] This invention provides a method for preparing alumina foam ceramics, comprising the following steps: S1. Polyurethane foam composite pretreatment: Take polyurethane foam and perform deep membrane removal treatment and hydrophilic modification treatment in sequence to obtain modified template.
[0024] In this embodiment, the deep membrane removal treatment step includes: subjecting the polyurethane foam to water bath heating treatment with an alkaline solution, wherein the alkaline solution is a sodium hydroxide solution with a concentration of 8–12 mol / L, for example, a concentration of 10 mol / L. The heating treatment is performed using a water bath at a temperature of 80–90°C for a duration of 5–7 hours; for example, at a temperature of 85°C for a duration of 6 hours.
[0025] In this embodiment, after removing the internal diaphragm, the process further includes cleaning and drying. Cleaning involves repeatedly rinsing with deionized water until neutral. Drying is performed by natural air drying.
[0026] In this embodiment, the hydrophilic modification step includes immersing the polyurethane foam after deep membrane removal treatment in a polymer solution at room temperature for 10–14 hours, for example, 12 hours. The polymer solution includes one or more of polyvinyl alcohol aqueous solution, polyvinylpyrrolidone aqueous solution, and hydroxyethyl cellulose. For example, the preparation of the polyvinyl alcohol aqueous solution includes heating polyvinyl alcohol and deionized water in a water bath until completely dissolved to obtain a polyvinyl alcohol aqueous solution.
[0027] This invention addresses the inherent characteristic of high surface tension in water-based slurries caused by the strong polarity of alumina powder. It innovatively proposes a composite pretreatment process: "high-concentration alkaline solution for high-temperature deep membrane removal + hydrophilic modification with water-soluble polymer" (e.g., membrane removal parameters: 10 mol / L NaOH, 85℃ water bath for 6 hours; modification parameters: 0.75 wt% PVA solution, room temperature soaking for 12 hours). This invention thoroughly removes the internal membrane of the foam that hinders the penetration of polar slurries through deep membrane removal, while the hydrophilic modification layer significantly reduces the contact angle between the template and the water-based slurry. This fundamentally solves the problems of slurry flow and missed coating caused by hydrophobic templates. This process design is perfectly adapted to the interfacial characteristics of polar alumina slurries, rather than a general template treatment method.
[0028] S2. Gradient Solid Content Slurry Preparation: Based on the requirements of the slurry application process, deionized water is used as the solvent, and alumina powder and sintering aids are used as the main raw materials. Dispersants and binders are added to prepare alumina slurries with different solid contents, including a primary slurry with a high solid content and at least one subsequent slurry with a low solid content.
[0029] The present invention provides a fixed ratio of main materials, sintering aids, binders, and dispersants, which are precisely adapted to gradient slurry coating and segmented sintering processes.
[0030] In this embodiment, the sintering aid is silicon dioxide; the binder is alkaline silica sol; and the dispersant is ammonium polyacrylate.
[0031] In this embodiment, when the slurry is applied twice, the alumina slurry with different solid contents includes: a primary slurry with a solid content of 60wt%–70wt%, and a secondary slurry with a solid content of 45wt%–55wt%. When the slurry is applied three times, the alumina slurry with different solid contents includes: a primary slurry with a solid content of 60wt%–70wt%, a secondary slurry with a solid content of 45wt%–55wt%, and a tertiary slurry with a solid content of 40wt%–50wt%.
[0032] In this embodiment, when the slurry solid content is 60wt%–70wt%, the mass ratio of alumina to silica as a sintering aid is 7–9:1–3. Based on the total mass of the alumina and silica powders, 3wt%–3.5wt% of alkaline silica sol is added as a binder, and 2wt%–4wt% of ammonium polyacrylate is added as a dispersant. When the slurry solid content is 45wt%–55wt%, the mass ratio of alumina to silica as a sintering aid is 7–9:1–3. Based on the total mass of the alumina and silica powders, 2wt%–3wt% of alkaline silica sol is added as a binder, and 1wt%–3wt% of ammonium polyacrylate is added as a dispersant. When the solid content of the slurry is 40wt% to 50wt%, the mass ratio of alumina to silica as a sintering aid is 7-9:1-3. Based on the total mass of alumina and silica powder, 2wt% to 3wt% of alkaline silica sol is added as a binder, and 1wt% to 3wt% of ammonium polyacrylate is added as a dispersant. As shown in Table 1.
[0033] Table 1 In this embodiment, the preparation of the alumina slurry includes: dissolving the binder and dispersant in deionized water, adding alumina and sintering aid, and then continuously stirring at a speed of 150–200 r / min for 4–8 hours. For example, the speed is 180 r / min and the stirring time is 6 hours.
[0034] S3. First-time slurry application, drying and pretreatment of the green body: The modified template is subjected to atmospheric pressure impregnation, centrifugal slurry application, and gradient segmented drying using the first-time slurry with high solid content; the dried green body is then subjected to either non-sintering, low-temperature sintering or first high-temperature sintering treatment.
[0035] In this embodiment, the atmospheric pressure impregnation and coating step in step S3 specifically includes: impregnating the coating slurry once by manual and / or centrifugal coating, so that the coating slurry is evenly coated on the surface of the modified template obtained in step S1.
[0036] In this embodiment, to avoid problems such as surface slurry cracking, peeling, green body collapse, and polyurethane foam template deformation caused by rapid evaporation of moisture after slurry application, the present invention adopts a gradient segmented drying process to dry the green body. The specific steps are as follows: A1. Room temperature pre-drying: Place the preform after centrifugal slurry treatment in a room temperature environment with natural ventilation for 10-14 hours (e.g., 12 hours). This step can slowly evaporate the surface moisture and allow the slurry to initially set.
[0037] A2. Low-temperature constant-temperature drying: Transfer the pre-dried blank into an oven and maintain it at a constant temperature of 55–75°C (e.g., 65°C) for 2–6 hours (e.g., 4 hours). This step can slowly remove internal adsorbed water and eliminate the humidity difference between the inside and outside.
[0038] A3. Thorough High-Temperature Drying: After low-temperature constant-temperature drying, raise the temperature to 110–130°C (e.g., 120°C) and maintain this temperature for 2–6 hours (e.g., 4 hours) until the quality of the green body is constant. This step thoroughly removes residual moisture, allowing the binder to fully cure.
[0039] In this embodiment, the low-temperature sintering step includes: heating the dried green body from 20°C to 150°C at a rate of 2-4°C / min, from 150°C to 180°C at a rate of 1-3°C / min, from 180°C to 220°C at a rate of 0.5-1.5°C / min, from 220°C to 250°C at a rate of 0.25-0.75°C / min, from 250°C to 420°C at a rate of 0.5-1.5°C / min, from 420°C to 650°C at a rate of 1-3°C / min, from 650°C to 950°C at a rate of 2-4°C / min, holding at 950°C for 1-3 hours, and cooling from 950°C to 500°C at a rate of 2-4°C / min, followed by furnace cooling.
[0040] S4. Subsequent slurry coating, drying, and sintering: Based on the preset target porosity and mechanical property requirements, the pretreated green body undergoes at least one subsequent slurry coating process, and the following steps are performed according to the pretreated state of the green body: S4.1 For the pre-treated green body selected in step S3, use a subsequent slurry with a low solid content to sequentially perform atmospheric pressure impregnation, centrifugal slurry application, and gradient staged drying before the first high-temperature sintering; or S4.2. For the green body pretreated by low-temperature sintering or first high-temperature sintering in step S3, use a subsequent slurry with a lower solid content for vacuum impregnation, centrifugal slurry application, and gradient segmented drying, followed by second high-temperature sintering; or S4.3. After completing step S4.1 or step S4.2 once, if the preset target porosity and mechanical properties are not achieved, step S4.2 is repeated with a slurry with a further reduced solid content for the next subsequent slurry application and second high-temperature sintering until the preset performance requirements are met, and the finished alumina foam ceramic product is obtained.
[0041] In this embodiment, the first high-temperature sintering includes a low-temperature polyurethane template removal stage and a first high-temperature sintering densification stage; the second high-temperature sintering only includes a second high-temperature sintering densification stage. Within the temperature range of 20–650°C, the heating rate of the second high-temperature sintering is higher than that of the first high-temperature sintering.
[0042] In this embodiment, the first high-temperature sintering step includes: heating the dried green body from 20°C to 150°C at a rate of 2-4°C / min, from 150°C to 180°C at a rate of 1-3°C / min, from 180°C to 220°C at a rate of 0.5-1.5°C / min, from 220°C to 250°C at a rate of 0.25-0.75°C / min, from 250°C to 420°C at a rate of 0.5-1.5°C / min, from 420°C to 650°C at a rate of 1-3°C / min, from 650°C to 1300°C at a rate of 2-4°C / min, holding at 1300°C for 1-3 hours, cooling from 1300°C to 500°C at a rate of 2-4°C / min, and cooling in the furnace.
[0043] In this embodiment, the second high-temperature sintering step includes: heating the dried green body from 20°C to 950°C at a rate of 4-6°C / min, heating it from 950°C to 1300°C at a rate of 2-4°C / min, holding it at 1300°C for 1-3 hours, cooling it from 1300°C to 500°C at a rate of 2-4°C / min, and cooling it in the furnace.
[0044] In this embodiment, the specific operations of vacuum impregnation and centrifugal slurry application in step S4 include: completely immersing the pre-treated green body (pre-treated by low-temperature sintering or first high-temperature sintering in step S3) in a subsequent slurry with a low solid content, and transferring it into a vacuum drying oven. The vacuum level is adjusted to 0.2–0.6 atm and maintained at that pressure for 10–20 minutes to allow the slurry to fully penetrate the green body. Subsequently, the green body is centrifuged at 100–300 r / min for 2–4 minutes to remove excess slurry from the surface and ensure uniform slurry distribution on the pore surface. The vacuum environment eliminates residual air within the green body's pores, reduces the apparent viscosity of the slurry, and achieves deep penetration and defect filling of the green body.
[0045] In this embodiment, the specific operations of atmospheric pressure impregnation and centrifugal slurry application in step S4 include: completely immersing the pre-treated green body (pre-treated for non-sintering in step S3) in a subsequent slurry with a low solid content, gently shaking it for 1-3 minutes until no obvious air bubbles escape, and then centrifuging it at 100-150 r / min for 1-3 minutes. This removes excess slurry from the surface of the green body and ensures that the slurry evenly coats the pores and surface of the green body. For non-sintering green bodies, the short-time shaking impregnation process can break the residual air film in the pores through mechanical disturbance, accelerate slurry wetting, and significantly shorten the impregnation time, effectively avoiding coating peeling during the impregnation process.
[0046] Addressing the core issue that the viscosity of alumina water-based slurry is exceptionally sensitive to changes in solid content, and that a single solid content slurry cannot simultaneously meet the requirements for skeleton construction and defect filling, this invention designs a slurry system with at least two levels of gradient solid content (e.g., a three-level gradient solid content slurry system, where slurry A is 68%, slurry B is 50%, and slurry C is 45%), coupled with a "gradient slurry application - differentiated impregnation - centrifugal slurry application" process. The high-solid-content slurry is used for a single application, enabling rapid construction of a continuous and complete three-dimensional ceramic skeleton. The medium / low-solid-content slurries combine fluidity and filling properties, effectively resolving the contradiction between the difficulty in penetration of high-solid-content slurries and the difficulty in adhesion of low-solid-content slurries. Combined with the centrifugal slurry application process, the slurry adhesion amount is precisely controlled, significantly avoiding the local pore-clogging problem caused by the high surface tension of alumina water-based slurry. This design precisely matches the rheological behavior characteristics of alumina slurry.
[0047] To address the inherent defects in the pore structure of alumina foam ceramics prepared by the organic foam impregnation method, such as thin ribs, hollowness, and interconnected micropores, this invention innovatively establishes a precise linkage and matching mechanism between the pretreatment state of the green body in the first slurry coating process and the subsequent slurry coating process. Based on the pore structure and surface characteristics of the green bodies in three different pretreatment states (non-sintering / low-temperature sintering / first high-temperature sintering), corresponding atmospheric pressure / vacuum impregnation slurry coating processes and centrifugal slurry coating parameters are adopted respectively to achieve targeted and precise repair of weak pore areas. This invention's linkage design of "green body state - slurry coating process" fundamentally solves the problems of fragile pore structure and insufficient mechanical properties in traditional processes.
[0048] The present invention also provides an alumina foam ceramic, which is obtained by the above-described method for preparing alumina foam ceramic.
[0049] In this invention, unless otherwise specified, all raw materials used in the preparation are commercially available products well known to those skilled in the art.
[0050] The present invention will be described in detail below through embodiments and experimental examples. However, these are merely examples and do not limit the present invention in any way.
[0051] Example 1: Preparation of alumina foam ceramics by a single slurry coating + a double slurry coating (single low-temperature sintering + double high-temperature sintering) Step 1: Pretreatment of polyurethane foam composite like Figure 1 As shown, all three types of pretreated green bodies undergo initial performance evaluation after secondary slurry application and corresponding sintering. If the preset target porosity and mechanical property requirements are not met, the next round of slurry application, drying, and sintering cycle begins. A re-evaluation is performed after each sintering cycle, and the finished alumina foam ceramic product is obtained once the standards are met. The process of this invention begins with the composite pretreatment stage of the polyurethane foam template. Polyurethane foam blocks with dimensions of 20cm × 30cm × 30cm are cut and immersed in a 10mol / L NaOH solution, then heated at a constant temperature of 85℃ for 6 hours to complete the deep membrane removal treatment. For example... Figure 2 As shown, the key differences between polyurethane foam before and after alkaline treatment are clearly presented: Figure 2 (a) is untreated raw polyurethane foam with a dense mesh membrane inside, which severely hinders the penetration and uniform coating of alumina water-based slurry; Figure 2 (b) The foam after high-concentration, high-temperature alkaline washing in this embodiment has had its internal diaphragm completely removed, and the pore connectivity has been greatly improved, providing a structural basis for the full penetration of subsequent slurry. After the membrane removal treatment is completed, the foam is repeatedly washed with deionized water until neutral, and then naturally dried before being immersed in a 0.75wt% polyvinyl alcohol (PVA) solution (3g PVA dissolved in 400mL deionized water) at room temperature for 12 hours to form a uniform hydrophilic modified layer on the foam surface. It is then drained and set aside for later use.
[0052] Step 2: Preparation of Gradient Solid Content Slurry in accordance with Figure 1 The process logic of "gradient slurry coating" is based on the rheological characteristics of alumina water-based slurry. Gradient solid content slurry A (68% solid content) and slurry B (50% solid content) are prepared respectively. The detailed formulation parameters are shown in Table 1. First, ammonium polyacrylate dispersant, alkaline silica sol binder and deionized water are mixed and stirred until completely dissolved. Powder raw materials are added at a mass ratio of alumina:silica = 8:2. Stirring is carried out continuously at a speed of 180 r / min for 6 hours to ensure that the powder and liquid phase are fully mixed. Finally, a stable slurry with no agglomeration and uniform dispersion is obtained.
[0053] Step 3: Gradient slurry coating-vacuum impregnation-centrifugal slurry coupling process This embodiment strictly follows Figure 1 The core process path (path 2: low-temperature sintering) is carried out in operation. (1) One-time coating: according to Figure 1 The "one-time slurry coating (slurry A)" step involves immersing the hydrophilically modified polyurethane foam into slurry A and using a centrifugal slurry coating method to initially coat the foam skeleton with slurry, laying the foundation for subsequent gradient slurry coating. (2) Gradient segmented drying: following Figure 1 The gradient segmented drying process shown is "pre-drying at room temperature for 12 hours → drying at 65°C for 4 hours → drying at 120°C for 4 hours". This process slowly removes free water and bound water from the slurry, avoiding coating shrinkage and cracking caused by rapid evaporation of moisture. (3) Low-temperature sintering: according to Figure 4 The low-temperature sintering regime curve shown (20-150℃ 3℃ / min→150-180℃ 2℃ / min→180-220℃ 1℃ / min→220-250℃ 0.5℃ / min→250-420℃ 1℃ / min→420-650℃ 2℃ / min→650-950℃ 3℃ / min→950℃ holding for 2h→950-500℃ -3℃ / min→furnace cooling) completes the thermal decomposition of polyurethane templates and the removal of organic additives; (4) Secondary slurry application: Immerse the sintered green body with primary slurry application into slurry B, and maintain pressure under a vacuum of 0.4 atm for 15 minutes to allow the slurry to fully penetrate into the pores; after removal, centrifuge at 200 r / min for 3 minutes to precisely remove excess slurry. Figure 3 As shown, the key differences between manual slurry application and centrifugal slurry application are clearly compared: Figure 3 (a) is the microstructure of the blank produced by traditional manual slurry application. The pores are thin, the slurry is unevenly distributed, there are local omissions and obvious traces of the template outline. Figure 3(b) is the blank after centrifugal slurry spinning in this embodiment. The pores are full and uniform, the slurry coating is complete and there is no clogging or missing coating, which fully demonstrates the advantage of centrifugal slurry spinning in precise control of the amount of alumina water-based slurry adhering to the surface. (5) Gradient segmented drying: Repeat the three-stage process of "room temperature pre-drying - low temperature drying - high temperature drying" to ensure that the slurry after secondary coating is completely cured and formed; (6) Second high-temperature sintering: according to Figure 6 The second high-temperature sintering regime curve shown (20-950℃ 5℃ / min→950-1300℃ 3℃ / min→1300℃ holding for 2h→1300-500℃ -3℃ / min→cooling with furnace) completes the necking and densification of alumina particles.
[0054] Finished product performance and morphology: The macroscopic morphology of the finished product shows no obvious problems such as blocked holes or missing pore ribs (overall appearance as shown). Figure 7 (b)); Figure 8 (b) Microscopic morphology shows that the pore structure is continuous and there are no obvious triangular hole defects; the performance test results are a porosity of 86.35% and a compressive strength of 2.24 MPa. Compared with the sample prepared by traditional process, the mechanical properties are improved by more than 1 times, and the porosity is still maintained in the high value range required for industrial application.
[0055] Example 2: Preparation of alumina foam ceramics by one-time slurry coating + two-time slurry coating + three-time slurry coating (one-time non-sintering + two-time high-temperature sintering + three-time high-temperature sintering) This embodiment adopts Figure 1 The core logic of path 1 (non-sintering) is implemented by combining a three-stage slurry coating design: Steps 1-2: Same as in Example 1, additionally prepare a low-solids-content gradient slurry C (solids content 45%); wherein the structural characteristics of the polyurethane template after alkali washing and hydrophilic modification are as follows. Figure 2 As shown in (b), the diaphragm is completely removed and its surface hydrophilicity is improved, ensuring continuous and uniform penetration of the slurry during multiple rounds of slurry application.
[0056] Step 3: Gradient slurry coating-vacuum impregnation-centrifugal slurry coupling process (1) One-time coating: according to Figure 1 The "one-time slurry coating (slurry A)" step involves immersing the hydrophilically modified polyurethane foam into slurry A, followed by centrifugal slurry removal. (2) Gradient segmented drying: following Figure 1 The gradient segmented drying process shown is “pre-drying at room temperature for 12 hours → drying at 65℃ for 4 hours → drying at 120℃ for 4 hours”. After the gradient segmented drying is completed, the green body is not sintered and the high porosity connectivity is retained. (3) Secondary slurry application: Immerse the non-sintering green body in slurry B, gently shake and soak for 2 minutes until no obvious air bubbles escape, then centrifuge at 125 r / min for 2 minutes to remove excess slurry from the surface of the green body and to evenly coat the pores and surface of the green body with slurry, followed by gradient staged drying. Compared to Example 1, the centrifugal speed is slightly increased to accommodate the increased slurry penetration, such as... Figure 3 As shown in (b), centrifugal slurry casting can effectively avoid slurry accumulation and pore blockage under high permeability conditions, compared to Figure 3 (a) The defects of manual slurry application are significantly reduced, while the uniformity of the pore reinforcement is improved. After slurry application, the slurry is cured using the gradient segmented drying process described in Example 1, and then... Figure 5 The first high-temperature sintering curve shown (20-150℃ 3℃ / min→150-180℃ 2℃ / min→180-220℃ 1℃ / min→220-250℃ 0.5℃ / min→250-420℃ 1℃ / min→420-650℃ 2℃ / min→650-1300℃ 3℃ / min→1300℃ holding for 2h→1300-500℃ -3℃ / min→furnace cooling) completes the densification of the green body; (4) Three-stage slurry coating: The sintered green body after two-stage slurry coating is immersed in slurry C, held under pressure at 0.4 atm vacuum for 15 min, and then centrifuged at 200 r / min for 2 min. The higher centrifugal speed is adapted to the high fluidity of the low solid content slurry, further optimizing the densification effect of the pores; after the slurry coating is completed, it is dried again in gradient stages, and then processed according to the attached... Figure 6 The second high-temperature sintering curve shown completes the high-temperature densification sintering at 1300℃.
[0057] Finished product performance and morphology: The macroscopic and microscopic morphology of the finished product is as follows Figure 7 As shown in (c) and 8(c), the pore diameter is larger and the pore rib fullness is better than that of Example 1, with no obvious triangular hole defects; the performance test results are a porosity of 79.17% and a compressive strength of 3.43MPa. Under the premise of maintaining high porosity, the mechanical properties can meet the high strength requirements of scenarios such as molten metal purification.
[0058] Comparative Example 1: Preparation of alumina foam ceramics by conventional single-stage slurry coating + one-step sintering (single high-temperature sintering) Using existing technology: Polyurethane foam is lightly defilmed by immersing it in 1 mol / L NaOH solution at 25°C for 1 hour (without hydrophilic modification). After treatment, the foam still retains its original properties. Figure 2 As shown in (a), a large amount of internal diaphragm residue severely hinders slurry penetration; the foam was immersed in a single alumina slurry with a solid content of 68%, and the slurry was applied manually (without vacuum impregnation or centrifugal slurry removal). After natural drying, it was directly heated to 1300℃ for sintering in one step (without segmented speed control), which completely disregarded the following procedures. Figure 1The core design includes gradient slurry application, segmented treatment, and centrifugal slurry control.
[0059] Finished product performance and morphology: The finished product shows obvious macroscopic problems such as incomplete coating of pores and localized pore blockage (e.g. Figure 7 (a) shows that the microstructure reveals thin pores and multiple triangular pore defects (e.g., Figure 8 (as shown in (a)); the final performance test result showed a porosity of 90.12%, but a compressive strength of only 1.12 MPa, and the mechanical properties were difficult to meet the requirements for industrial use.
[0060] Compared with Comparative Example 1, the core technical advantages of Examples 1 and 2 can be verified through a complete and closed-loop system of accompanying drawings: Firstly, Figure 2 It has been confirmed that the pretreatment of "high-concentration high-temperature alkaline washing + hydrophilic modification" can completely remove the internal mesh membrane of the template, thus solving the fundamental problem of obstructed penetration of alumina water-based slurry from a structural level; secondly, Figure 3 This visually demonstrates the significant improvement in coating uniformity achieved by the coupled "vacuum impregnation + centrifugal slurry" process, effectively avoiding defects such as thinner pores, missed coating, and pore blockage caused by traditional manual slurry application; thirdly, Figure 9 By comparing the porosity and compressive strength data of samples prepared by different processes, the superiority of the process of the present invention is quantitatively confirmed. The samples of Examples 1 and 2, while maintaining a high porosity of over 79%, achieved compressive strengths of 2.24 MPa and 3.43 MPa, respectively, which are far higher than the comparative example (porosity of 90% but compressive strength of only 1.12 MPa), fully demonstrating the synergistic improvement effect of porosity and mechanical properties.
[0061] This invention achieves synergistic optimization of the entire process—"template modification - gradient slurry application - vacuum centrifugal slurry control - segmented sintering"—fundamentally solving the problem of poor interface compatibility between alumina water-based slurry and polyurethane templates, and the difficulty in precisely controlling the slurry application rate, leading to uncontrolled pore structure. Furthermore, it effectively repairs inherent defects in the pore structure through a gradient reinforcement mechanism, overcoming the technical bottleneck of traditional processes that cannot simultaneously achieve high porosity and high strength. Moreover, by combining different centrifugal speeds and slurry application times, it can be tailored to specific needs. Figure 9 The performance data can be flexibly adapted to the performance requirements of different application scenarios, such as molten metal filtration (high porosity) and catalyst support (high strength).
[0062] Various embodiments of the present invention may exist in the form of a range; it should be understood that the description in the form of a range is merely for convenience and brevity and should not be construed as a hard limitation on the scope of the invention; therefore, it should be considered that the range description has specifically disclosed all possible subranges and single numerical values within that range. For example, it should be considered that the range description from 1 to 6 has specifically disclosed subranges such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., and single numbers within the range, such as 1, 2, 3, 4, 5, and 6, regardless of the range. Furthermore, whenever a numerical range is referred to herein, it means including any referenced number (fraction or integer) within the range referred to.
[0063] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A method for preparing alumina foam ceramic, characterized in that, Includes the following steps: S1. Polyurethane foam composite pretreatment: Take polyurethane foam and perform deep membrane removal treatment and hydrophilic modification treatment in sequence to obtain modified template. S2. Gradient solid content slurry preparation: According to the requirements of the slurry coating process, deionized water is used as solvent, alumina powder and sintering aid are used as main raw materials, and dispersants and binders are added to prepare alumina slurries with different solid contents, including a primary slurry with a high solid content and at least one subsequent slurry with a low solid content. S3. Primary slurry application, drying and pretreatment of the green body: The modified template is subjected to atmospheric pressure impregnation, centrifugal slurry application, and gradient segmented drying using the primary slurry with high solid content; the dried green body is then subjected to either non-sintering, low-temperature sintering, or first high-temperature sintering treatment. S4. Subsequent slurry coating, drying, and sintering: Based on the preset target porosity and mechanical property requirements, the pretreated green body undergoes at least one subsequent slurry coating process, and the following steps are performed according to the pretreated state of the green body: S4.1 For the pre-treated green body selected in step S3, use a subsequent slurry with a low solid content to sequentially perform atmospheric pressure impregnation, centrifugal slurry application, and gradient staged drying before the first high-temperature sintering; or S4.
2. For the green body pretreated by low-temperature sintering or first high-temperature sintering in step S3, use a subsequent slurry with a lower solid content for vacuum impregnation, centrifugal slurry application, and gradient segmented drying, followed by second high-temperature sintering; or S4.3 After completing step S4.1 or step S4.2, if the preset target porosity and mechanical properties are not achieved after one subsequent slurry application and corresponding sintering, step S4.2 is repeated with a slurry having a further reduced solid content to perform the next subsequent slurry application and second high-temperature sintering until the preset performance requirements are met, and the finished alumina foam ceramic product is obtained. Wherein, the first high-temperature sintering includes a low-temperature polyurethane template removal stage and a first high-temperature sintering densification stage, and the second high-temperature sintering only includes a second high-temperature sintering densification stage. Within the temperature range of 20–650℃, the heating rate of the second high-temperature sintering is higher than that of the first high-temperature sintering.
2. The preparation method according to claim 1, characterized in that, In step S1, the deep membrane removal process includes: The polyurethane foam was subjected to water bath heating treatment with an alkaline solution; wherein the alkaline solution was a sodium hydroxide solution with a concentration of 8-12 mol / L, the water bath heating temperature was 80-90℃, and the water bath heating time was 5-7 hours. The steps of hydrophilic modification treatment include: The polyurethane foam after deep membrane removal treatment is immersed at room temperature using a polymer solution; the immersion time is 10-14 hours, and the polymer solution includes one or more of polyvinyl alcohol aqueous solution, polyvinylpyrrolidone aqueous solution, and hydroxyethyl cellulose.
3. The preparation method according to claim 1, characterized in that, The sintering aid is silicon dioxide; The adhesive is an alkaline silica sol; The dispersant is ammonium polyacrylate.
4. The preparation method according to claim 3, characterized in that, When the slurry is applied twice, the alumina slurry with different solid contents includes: a primary slurry with a solid content of 60wt% to 70wt%, and a secondary slurry with a solid content of 45wt% to 55wt%. When the slurry is applied three times, the alumina slurry with different solid contents includes: a primary slurry with a solid content of 60wt% to 70wt%; a secondary slurry with a solid content of 45wt% to 55wt%; and a tertiary slurry with a solid content of 40wt% to 50wt%.
5. The preparation method according to claim 4, characterized in that, When the solid content of the slurry is 60wt% to 70wt%, the mass ratio of alumina to silica as a sintering aid is 7 to 9: 1 to 3. Based on the total mass of the alumina and silica powders, 3wt% to 3.5wt% of alkaline silica sol is added as a binder, and 2wt% to 4wt% of ammonium polyacrylate is added as a dispersant. When the solid content of the slurry is 45wt% to 55wt%, the mass ratio of alumina to silica as a sintering aid is 7 to 9: 1 to 3. Based on the total mass of the alumina and silica powders, 2wt% to 3wt% of alkaline silica sol is added as a binder, and 1wt% to 3wt% of ammonium polyacrylate is added as a dispersant. When the solid content of the slurry is 40wt% to 50wt%, the mass ratio of alumina to silica as a sintering aid is 7 to 9: 1 to 3. Based on the total mass of alumina and silica powder, 2wt% to 3wt% of alkaline silica sol is added as a binder, and 1wt% to 3wt% of ammonium polyacrylate is added as a dispersant.
6. The preparation method according to claim 1, characterized in that, The preparation of the alumina slurry includes: The binder, dispersant and deionized water are mixed and dissolved, alumina and sintering aid are added and mixed, and then stirred continuously at 150-200 r / min for 4-8 hours.
7. The preparation method according to claim 1, characterized in that, The atmospheric pressure impregnation and slurry application step in step S3 specifically includes: The slurry is applied manually and / or by centrifugal coating to ensure that the slurry is evenly coated on the surface of the modified template prepared in S1. The steps of atmospheric pressure impregnation and centrifugal slurry removal in step S4 specifically include: The pre-treated green body from step S3 is completely immersed in the subsequent slurry with a low solid content. It is gently shaken and immersed for 1-3 minutes until no obvious air bubbles escape. Then, it is centrifuged at 100-150 r / min to remove the slurry. In 1 to 3 minutes, excess slurry on the surface of the billet is removed, and the subsequent slurry is evenly coated on the pores and surface of the billet. The vacuum impregnation and centrifugal slurry application steps in step S4 specifically include: The green body, which has undergone low-temperature sintering or first high-temperature sintering pretreatment in step S3, is completely immersed in at least one subsequent slurry and transferred into a vacuum drying oven. The vacuum level is adjusted to 0.2–0.6 atm and held for 10–20 minutes to allow the subsequent slurry to fully penetrate the green body. Then, the green body is centrifuged at 100–300 r / min for 2–4 minutes to remove excess slurry from the surface of the green body and to ensure uniform distribution of slurry on the surface of the pores. The vacuum environment can eliminate residual air in the pores of the green body, reduce the apparent viscosity of the slurry, and achieve deep penetration of the slurry into the green body and filling of defects.
8. The preparation method according to claim 1, characterized in that, The gradient segmented drying step includes: A1. Room temperature pre-drying: Place the blank after centrifugal slurry treatment in a room temperature environment with natural ventilation and let it stand for 10-14 hours; A2. Low-temperature constant temperature drying: Transfer the pre-dried blank into the drying oven and keep it at a constant temperature of 55-75℃ for 2-6 hours. A3. High-temperature thorough drying: After low-temperature constant-temperature drying, the billet is heated to 110-130℃ and kept at a constant temperature for 2-6 hours until the quality of the billet is constant.
9. The preparation method according to claim 1, characterized in that, The low-temperature sintering step includes: The dried billet is heated from 20°C to 150°C at a rate of 2–4°C / min, from 150°C to 180°C at a rate of 1–3°C / min, from 180°C to 220°C at a rate of 0.5–1.5°C / min, from 220°C to 250°C at a rate of 0.25–0.75°C / min, from 250°C to 420°C at a rate of 0.5–1.5°C / min, from 420°C to 650°C at a rate of 1–3°C / min, from 650°C to 950°C at a rate of 2–4°C / min, held at 950°C for 1–3 hours, and then cooled from 950°C to 500°C at a rate of 2–4°C / min, and cooled in the furnace. The first high-temperature sintering step includes: The dried billet is heated from 20°C to 150°C at a rate of 2–4°C / min, from 150°C to 180°C at a rate of 1–3°C / min, from 180°C to 220°C at a rate of 0.5–1.5°C / min, from 220°C to 250°C at a rate of 0.25–0.75°C / min, from 250°C to 420°C at a rate of 0.5–1.5°C / min, from 420°C to 650°C at a rate of 1–3°C / min, from 650°C to 1300°C at a rate of 2–4°C / min, held at 1300°C for 1–3 hours, and then cooled from 1300°C to 500°C at a rate of 2–4°C / min, and cooled in the furnace. The second high-temperature sintering step includes: The dried billet is heated from 20°C to 950°C at a rate of 4–6°C / min, then heated from 950°C to 1300°C at a rate of 2–4°C / min, held at 1300°C for 1–3 hours, and then cooled from 1300°C to 500°C at a rate of 2–4°C / min, and cooled in the furnace.
10. An alumina foam ceramic, characterized in that, The alumina foam ceramic is obtained by the preparation method of alumina foam ceramic according to any one of claims 1 to 9.